Does Glucagon Stimulation Test Help to Predict Autoimmunity in Newly Diagnosed Non Obese Adults with Diabetes? - Rogowicz-Frontczak, A.; Zozulińska-Ziółkiewicz, D.; Niedźwiecki, P.; Litwinowicz, M.; Wierusz-Wysocka, B. (Experimental and Clinical Endocrinology & Diabetes, 2012)
Classification of diabetes type in adults patients remains difficult. This study was undertaken to determine the relationship between presence of autoantibodies in the serum and the result of glucagon stimulation test in non obese patients at aged above 35 years with newly diagnosed diabetes.Study involved 52 non obese adults aged 42 years [interquartile range (IQR): 37–46], with body mass index (BMI) 23.7 kg/m2 (IQR: 21.4–26.2). Presence of autoantibodies to islet cells (ICA), antibodies to tyrosine phosphatase (IA-2), glutamic acid decarboxylase autoantibodies (anti-GAD) and plasma fasting and stimulating (6 min after intravenous injection of 1 mg glucagon) C-peptide level was assessed.73.1% subjects had at least 1 of 3 assessed autoantibodies, 26.9% patients were autoantibodies negative. According to serum C-peptide concentration after stimulation test with glucagon patients were divided into 2 groups. Receiver Operating Characteristic (ROC) Curve for determination of an optimal cut-point (C-peptide stimulation above and below 1.6) was used. In patients with negative stimulation test higher prevalence of 2 (33.3% vs. 66.7%; p=0.04) or 3 (12.5% vs. 87.5%, p=0.01) positive autoantibodies was noticed in comparison to patients with positive stimulation test. Multivariate logistic regression showed that presence of autoantibodies was independently associated with stimulated C-peptide level (OR 2.3; 95%CI: 1.07–5.28, p=0.03).Autoimmune diabetes should be suspected in subjects with lower response of β- cell in glucagon stimulation test. If the C-peptide do not increase more than 1.6 after glucagon presence of autoanibodies is more probable.
Keywords: autoimmunity; antibodies; diabetes